Preparation of iron/calcium-modified biochar for phosphate removal from industrial wastewater. (10th January 2023) - Ou, Wenjuan; Lan, Xin; Guo, Jing; Cai, Aimin; Liu, Peng; Liu, Na; Liu, YingYing; Lei, Yutao
Abstract: Phosphorous pollution is one of the main factors causing water eutrophication. For the treatment of wastewater, metal-modified biochar has emerged as a promising adsorbent with enhanced affinity for anions such as phosphate. Biochar modified with Fe or Ca are suitable for the treatment of low-concentration phosphorous wastewater (<100mg/L). However, the use of modified biochar to remove high concentrations of phosphate from industrial wastewater is challenging. In this study, biochar from poplar wood, wheat bran, bagasse, and bamboo were prepared and loaded with Fe and Ca, and its adsorption performance and degradation mechanism in the presence of high phosphate concentrations were investigated. The phosphate adsorption capacity of the Fe/Ca-modified biochar was 12–70 times higher than that before the modification. The best type of biochar for phosphate removal was iron/calcium oxide-modified bamboo biochar (ZFCO-BC) through batch experiments. X-ray diffraction (XRD) and X-ray absorption near-edge structure (XANES) analyses showed that ZFCO-BC reacted with wastewater to produce stable vivianite (Fe3 (PO4 )2 ·(H2 O)8 ), which did not cause secondary release. ZFCO-BC exhibited a synergistic effect on the removal of 21 metals, including Cr, Cu, Co, Cd, As, Pb, and Y, from complex polluted water. Meanwhile, after 48 h of reaction, the concentration of phosphate decreased from 1660 to 0.061 mg/L, and the final value in the wastewater was lower than the phosphate discharge index indicated by the GB T31962-2015 Sewage Discharge into Urban sewer Water Quality Standard. This study shows that a single remediation system based on ZFCO-BC can remove phosphate and multiple heavy metals from contaminated water, providing a cost-effective treatment solution for complex polluted water bodies, such as industrial wastewater and groundwater. Graphical abstract: Image 1 Highlights: A novel iron/calcium-modified biochar was prepared. Biochar can remove 1660 mg/L phosphate from complex industrial wastewater. 21 harmful metal ions are removed from industrial wastewater simultaneously. Phosphate is removed via the formation and precipitation of Fe3 (PO4 )2 ·(H2 O)8 .